CONVENTIONAL AND UNCONVENTIONAL RAILWAY TRACK FOR RAILWAYS ON SOFT GROUND IN INDONESIA (Case Study: Rantau Prapat-Duri Railways Development) - , DIAN SETIAWAN M. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Riau province has a more than 1.7 million hectare of peatland and soft ground. Approximately 80.7% of this area has the depth more than 2 meter. Peat land and soft ground have low bearing capacity which is not favorable for civil construction. Therefore, the appropriate railway track system design on soft ground becomes essentials. The objective of this research is to determine the most appropriate and the most efficient of railway track system for railway systems development in Riau Province. This research discusses the comparative study between conventional track and unconventional (slab) track systems design which is laid on soft ground. The data and important informations related to the topic were gained from Final Report of Rantau Prapat-Duri Railway System Designs by DGR (2006), International Railways and Indonesian Railways Regulation, various books, MSc Reports, Civil Engineering Journals, and verified internet sources. All the information is combined and completed each other in order to discuss the material requirement of railway track design, to calculate the thickness requirement of railway track design, to review the advantages and disadvantages of railway track design, and to discuss and calculate the economic efficiency, construction costs, and maintenance costs of railway track. Rheda 2000 system was selected as unconventional (slab) track design and was also considered as an alternative, which has a longer life cycle, higher structural track stability, lower maintenance need, and lower thickness requirement. However, the slab track construction cost is more expensive than conventional track. It requires homogeneous subgrade with no settlement, and it is not economically efficient in unstable circumstances with additional measures being taken for the substructure. The additional cost required for the use of slab track in the open to limit long-term settlement in the substructure is higher than for conventional track by the factor 2-2.5. The results show that the conventional track is the most proper and the most efficient railway track system to be applied for Rantau PrapatâDuri railway systems. It is a better solution in earth structures since it has a high flexibility of the track and much lower construction cost. It also requires much lower material requirement than for slab track. It provides more accurate corrections and faster maintenance. It is suggested to conduct a software program analysis to calculate the embankment construction stability for slab track design. A better subballast and ballast properties should be used for conventional track system to reduce the thickness requirements and to increase the construction stability. A slab track could be a solution for Indonesian railway systems development in the future. The author underlines the need for further research to investigate and to prove the advantages of a better subballast and ballast properties for conventional track system. However, the economic efficiency analysis also should be conducted related to the materials availability and extensive mass transportation.